Commentary: Brain-to-Brain Synchrony Tracks Real-World Dynamic Group Interactions in the Classroom and Cognitive Neuroscience: Synchronizing Brains in the Classroom - Parada, Francisco J.; Rossi, Alejandra (Frontiers in human neuroscience, 2017)
Most social cognition studies investigate behavior and concomitant brain activity of isolated individuals while exposed to stimuli of social relevance (e.g., facial and/or bodily gestures as in Thompson et al., 2007), social nature (e.g., facial expression of emotions as in Vuilleumier and Pourtois, 2007), or immerse in a social context (e.g., increased number of individuals within the stimuli as in Akitsuki and Decety, 2009; Puce et al., 2013) without actually involving a real interaction with another person (i.e., simulated interactions as in Caruana et al., 2016). [...]in order to better study the neural basis of situated and embodied social interaction, we suggest that each study contributing to the referred paradigmatic shift should be evaluated (a priori or a posteriori) considering two main challenges depicted in Figure 1: (i) The theoretical need of developing a coherent framework for interpreting results and mapping the whole spectrum of relations between personal, social, and neural dynamics. (ii) The methodological need, referring to the relationship between the ever-improving data-acquisition technologies and the actual usage plausibility of such technologies at a single-subject and/or group level. Recent evidence indicates that although the current technical landscape is very promising, we must proceed with caution (Melnik et al., 2017). [...]we would like to point out that “more naturalistic” data acquisition can be equally undertaken using both consumer-grade, as in Dikker et al. [...]we would like to stress that, contrary to Bhattacharya (2017), we believe consumer-grade technologies are not the natural next step outside “synthetic laboratory settings,” but a parallel path facing similar, if not larger, technical and analytical requirements that research-grade technologies confront (Figure 1). [...]in times of paradigmatic change, with new and exciting theoretical vistas encompassed within the embodied social cognition framework and new available technologies, social neuroscience wants to be methodologically cautious and remember that research questions and epistemological views guide our work.